Genetic evaluation of climate resilient sugarcane clones under waterlogged condition - K. Karthik*, S. Rakshitha and D.N. Kamat (Electronic Journal of Plant Breeding)
Waterlogging, an abiotic stress situation, affects sugarcane yields by 15-20 percent. The present study sought to identify sugarcane clones suitable for waterlogging conditions. Fifteen climate resilient sugarcane clones and three standard check varieties were evaluated under waterlogged as well as normal conditions at Kalyanpur Research farm, RPCAU, in a alpha lattice. Variance analysis revealed that the studied characters differ significantly among resilient sugarcane clones under waterlogging conditions. High variability was found for cane height at maturity. Commercial Cane Sugar(t/ha) had high GCV and the trait, number of nodes with aerial roots had higher PCV under waterlogged conditions. Less variability was observed for all quality traits such as brix, purity, and sucrose percent at 10 and 12 months, CCS%, Pol percent cane and juice extraction percent at harvest. High to moderate heritability along with moderate genetic advance was found for majority of the traits indicating that the choice of these characters will be suitable for successful crop improvement. Commercial cane sugar (t/ha) had high heritability and high genetic advance which suggests that direct selection for this character can be indicator under waterlogged conditions.